2019
DOI: 10.3390/su11236766
|View full text |Cite
|
Sign up to set email alerts
|

Compassion and Job Performance: Dual-Paths through Positive Work-Related Identity, Collective Self Esteem, and Positive Psychological Capital

Abstract: The purpose of this study is to examine the unexplored mechanisms through which employee job performance is affected by compassion experienced at work. While the relationship between compassion and job performance is relatively well established in the literature, our knowledge of the actual mechanisms underlying this relationship is still in a nascent state. In this study, we propose two paths through which increased job performance results from workplace compassion. Our empirical results, obtained through 360… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 58 publications
(104 reference statements)
1
29
0
1
Order By: Relevance
“…Al mismo tiempo, el capital psicológico fomenta la motivación, el compromiso con el trabajo y el rendimiento en el profesorado. Estos resultados son similares a los descritos en otros profesionales y en estudiantes, y demuestran la importancia de desarrollar el capital psicológico para promover el buen desempeño (Carmona-Halty et al, 2019;Ko y Choi, 2019;Soni y Rastogi, 2019;Tisu et al, 2020;Xi et al, 2020). En este sentido, se defi ende que la confi anza en lograr los objetivos y el éxito y la creencia en las propias capacidades que caracterizan al capital psicológico propician la motivación y el rendimiento (Carter y Youssef-Morgan, 2019;Newman, Ucbasaran, Zhu y Hirst, 2014;Youssef-Morgan y Luthans, 2015).…”
Section: Discussionunclassified
“…Al mismo tiempo, el capital psicológico fomenta la motivación, el compromiso con el trabajo y el rendimiento en el profesorado. Estos resultados son similares a los descritos en otros profesionales y en estudiantes, y demuestran la importancia de desarrollar el capital psicológico para promover el buen desempeño (Carmona-Halty et al, 2019;Ko y Choi, 2019;Soni y Rastogi, 2019;Tisu et al, 2020;Xi et al, 2020). En este sentido, se defi ende que la confi anza en lograr los objetivos y el éxito y la creencia en las propias capacidades que caracterizan al capital psicológico propician la motivación y el rendimiento (Carter y Youssef-Morgan, 2019;Newman, Ucbasaran, Zhu y Hirst, 2014;Youssef-Morgan y Luthans, 2015).…”
Section: Discussionunclassified
“…For example, experienced compassion can serve as personal resources to increase one's self-regulation [34]. In addition, employees who experience compassion at work (i.e., who perceive they are genuinely cared about by others) are likely to form collective self-esteem, as well as a positive work-related identity, which, in turn, increases their job performance [35]. It can also lead to more constructive work behaviors, such as voice behaviors, because employees who experience compassion at work are likely to have high levels of affective commitment, which, in turn, facilitates constructive behaviors [36].…”
Section: Compassion and Positive Emotionmentioning
confidence: 99%
“…Empirical findings from previous research have supported this argument. For example, giving and receiving compassion in relationships among colleagues, subordinates, and superiors is related to positive emotions; compassion not only enhances positive emotions in organizational members but also has a positive effect on improving job performance [4,28,35,38] because positive emotions energize productive performance by strengthening the emotional bond among employees. This is congruent with Bono and Ilies's [39] argument which states that helping employees experience positive emotions is one of the important psychological processes affecting individuals' productive outcomes.…”
Section: Compassion and Positive Emotionmentioning
confidence: 99%
“…Specifically, this study seeks to examine the mediating roles of compassion and positive emotions at work as a missing linkage in the relationship between positive leadership and organizational identification. Given that not much empirical studies have been conducted on compassion at work (Ko & Choi, 2019), this study seeks to shed light on the positive roles of compassion in the workplace.…”
Section: Aimsmentioning
confidence: 99%
“…Regarding the roles of compassion in organizations, sinceLilius et al (2008) have developed the measurement items for compassion at work, previous studies demonstrated the causal relationships between positive organizational constructs and compassion (e.g.,Ko & Choi, 2019;Lilius et al, 2008). For example,…”
mentioning
confidence: 99%